Decision Support System and Managerial Decision Quality in Production Contexts: A Systematic Literature Review - Alam Avrianto (SAINTEKS : Jurnal Sain dan Teknik, 2026)
Globalization and digitalization have transformed production systems, requiring managers to make strategic decisions swiftly and accurately. Decision Support Systems (DSS) have emerged as technological solutions to support this process; however, studies examining their impact on managerial decision quality remain limited. This research aims to analyze and synthesize the literature on the role of DSS in enhancing managerial decision quality within modern production organizations. A Systematic Literature Review (SLR) guided by PRISMA protocols was conducted using articles published between 2015 and 2025. From an initial pool of 200 articles retrieved from Google Scholar, 50 studies met the inclusion criteria and were analyzed using bibliometric techniques, thematic analysis, and narrative synthesis. The systematic analysis reveals that most studies focus on technical aspects such as algorithmic efficiency and artificial intelligence integration, while psychological dimensions of users and managerial decision quality are rarely addressed. This study proposes a conceptual framework that integrates DSS capabilities, user interaction, and decision process quality as the foundation for developing DSS that are more adaptive and human-centered. The findings not only contribute theoretically but also highlight opportunities for future empirical research to evaluate how DSS can enhance managerial decision quality and support modern production practices.